198k views
3 votes
Solve each system by elimination.
1) -x + 3y = -2
x - 2y=3

2 Answers

4 votes

Add the equations in order to solve for the first variable. Plug this value into the other equations in order to solve for the remaining variables.

Point Form:

(5,1)

Equation Form:

x=5 , y=1

User Mike Dour
by
4.8k points
6 votes

Answer:

x=5, y= 1

Explanation:

-x + 3y = -2

x - 2y=3

Add the two equations together

-x + 3y = -2

x - 2y=3

-------------------------

y = 1

Now we can find x

x -2y = 3

x - 2(1) =3

x-2 =3

Add 2 to each side

x-2+2= 3+2

x = 5

User Manabu
by
5.1k points